Protecting electrical equipment new practices for preventing high altitude electromagnetic pulse impacts - Gurevich, Vladimir, 1956- (Walter de Gruyter GmbH, 2021)
How do you protect electrical systems from high energy electromagnetic pulses? This book completes the overview of systems and practices against EMPs from high altitude sources started with the previous "Protecting Electrical Equipment : Good practices for preventing high altitude electromagnetic pulse impacts", including practical protection methods and means for evaluating their effectiveness.